Effectiveness of Sublingual Immunotherapy in the Treatment of HDM-Induced Nasobronchial Allergies: A 3-Year Randomized Case-Control Study From Kashmir - Baba, Shahid M.; Rasool, Roohi; Gull, Ayaz; Qureshi, Taha A.; Beigh, Afaq H.; Qadri, Qurteeba; Shah, Zafar A. (Frontiers in Immunology, 2021)
Allergen immunotherapy (AIT) is the only disease modifying treatment for allergic disorders that induces immunological tolerance through administration of specific allergens. Studies on AIT for subcutaneous route are in abundance, however, efficacy of AIT in tablet form through sublingual route has not been well elucidated. The present prospective, parallel-group, controlled study sought to compare the efficacy of sublingual immunotherapy tablets with pharmacotherapy (PT) in 332 house dust mite (HDM) induced allergic asthma and/or rhinitis patients over a period of 3 years. Patients were followed up for a 6 months run-in period and then randomly stratified as those who would receive sublingual immunotherapy (SLIT), sublingual immunotherapy in addition to pharmacotherapy (SLIT+PT) and pharmacotherapy (PT) alone. AIT was administered in the form of sublingual tablets. Symptom and medication scores were measured every 3 months. In vitro evaluation of serum total and house dust mite specific immunoglobulin E (HDM-s IgE) levels was carried out every 3 months whileas, in vivo skin-prick test was performed annually for 3 years. Our study demonstrated sustained clinical improvement, reduction in ICS dose and duration as well as prevention from development of neosensitization to other aero allergens in HDM-allergic asthmatics and/or rhinitis patients treated with 3 years SLIT. Despite a remarkable clinical improvement with AIT, we observed that SLIT did not significantly change the skin reactivity to HDM at 3 years and also there was no significant change in the ratio of serum total and HDM specific IgE. Given the immune and disease modifying effects of AIT in allergic diseases, the present study supports the notion of its sublingual mode being an effective long term immunomodulator in HDM-sensitized naso-bronchial allergies.